Implementation of Child Protection and Development Policies in the Makassar City - Muh. Nasrullah; Muhammad Luthfi Siraj (Program Pascasarjana Universitas Negeri Makassar, 2023)
This research aims to determine how the government implements policies for protecting and developing children in Makassar City. The research method used is qualitative to examine the relationship between variables. Data collection techniques include interviews and documentation. The data analysis technique follows the steps outlined in the theories of Miles, Huberman, and Saldana, which involve data condensation, data presentation, and drawing conclusions or verification. The research findings based on interviews and observations indicate that the implementation is not efficient and effective in terms of human resources. According to Edwards III's theory, efficient and effective implementation requires sufficient resources. Therefore, Makassar Mayor Regulation Number 45 of 2020, which aims to provide support for street children, has not been fully optimized because the Department of Women's Empowerment and Child Protection still needs more optimized resources, especially in terms of budget allocation. However, when considering the indicators of communication, disposition, and bureaucratic structure, the implementation is deemed fairly effective, as all four dimensions are functioning as intended.